2007
DOI: 10.1017/s0954579407070058
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory and suggestibility in children with autism spectrum disorder

Abstract: Two paradigms were developed to examine autobiographical memory (ABM) and suggestibility in children with autism spectrum disorder (ASD). Children with ASD (N = 30) and typically developing chronological age-matched children (N = 38) ranging in age from 5 to 10 years were administered an ABM questionnaire. Children were asked about details of current and past personally experienced events. Children also participated in a staged event, and later were provided with true and false reminders about that event. Late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
131
3
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 47 publications
11
131
3
3
Order By: Relevance
“…As mentioned in the introduction, despite the fact that all previous studies used homogeneous samples of high-functioning adults with ASD, their findings regarding both the completeness and accuracy of eyewitness testimony to date are mixed. Our findings of similar levels of completeness of the reports of witnesses with RUNNING HEAD: Experienced eyewitness events in ASD 21 ASD to their typical counterparts are consistent with some existing studies (e.g., Maras & Bowler, 2010; but inconsistent with others (e.g., Bruck et al, 2007;Maras & Bowler, 2011;McCrory et al, 2007). It could be concluded from the present findings that individuals with ASD recall more details if the event is salient, live and personally participated in, but given the inconsistent findings previously reported, future work is needed to clarify and confirm this interpretation.…”
Section: Completeness and Accuracy Of Recallsupporting
confidence: 88%
See 3 more Smart Citations
“…As mentioned in the introduction, despite the fact that all previous studies used homogeneous samples of high-functioning adults with ASD, their findings regarding both the completeness and accuracy of eyewitness testimony to date are mixed. Our findings of similar levels of completeness of the reports of witnesses with RUNNING HEAD: Experienced eyewitness events in ASD 21 ASD to their typical counterparts are consistent with some existing studies (e.g., Maras & Bowler, 2010; but inconsistent with others (e.g., Bruck et al, 2007;Maras & Bowler, 2011;McCrory et al, 2007). It could be concluded from the present findings that individuals with ASD recall more details if the event is salient, live and personally participated in, but given the inconsistent findings previously reported, future work is needed to clarify and confirm this interpretation.…”
Section: Completeness and Accuracy Of Recallsupporting
confidence: 88%
“…McCrory et al (2007) used a live classroom event and reported that whilst children with ASD freely recalled around a third less information than typically developing children did, they were no less accurate with regards to the proportion of errors or incorrect details that they reported. Bruck et al (2007) also reported that ASD children reported fewer correct details than comparison children in response to both free recall and specific questions about a previously witnessed magic show. Of the studies with adults, none to date have used a live eyewitness event, or an event in which the witness has actively participated.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Blair, Frith, Smith, Abell, & Cipolotti, 2002), in the episodic recollection of personally experienced events (e.g. Bruck, London, Landa, & Goodman, 2007), and in the organisation of information in memory (Bowler, Gardiner, Grice, & Saavalainen, 2000;Bowler, Matthews, & Gardiner, 1997;Tager-Flusberg, 1991). They also sometimes struggle to recall where, when, how or from whom they learnt something (Bowler, Gardiner, & Berthollier, 2004;Bennetto et al, 1996), and both neural and theoretical perspectives suggest that individuals with ASD experience difficulties in binding elements of an experience together in memory (e.g.…”
mentioning
confidence: 99%